Hydroeconomic modeling for assessing water scarcity and agricultural pollution abatement policies in the Ebro River Basin, Spain. (10th December 2021) - Baccour, Safa; Albiac, Jose; Kahil, Taher; Esteban, Encarna; Crespo, Daniel; Dinar, Ariel
Abstract: Water scarcity and water quality degradation are major problems in many basins across the world, especially in arid and semiarid regions. The severe pressures on basins are the consequence of the intensification of food production systems and the unrelenting growth of population and income. Agriculture is a major factor in the depletion and degradation of water resources, and contributes to the emissions of greenhouse gases (GHG). Our study analyzes water allocation and agricultural pollution into watercourses and the atmosphere, with the purpose of identifying cost-effective policies for sustainable water management in the Ebro River Basin (Spain). The study develops an hydroeconomic model that integrates hydrological, economic and water quality aspects, capturing the main spatial and sectoral interactions in the basin. The model is used to analyze water scarcity and agricultural pollution under normal and droughts conditions, providing information for evaluating mitigation and adaptation policies. Results indicate that drought events increase nitrate concentration by up to 63% and decrease water availability by 42% at the mouth of Ebro River, highlighting the tradeoffs between water quantity and quality. All mitigation and adaptation policies reduce the effects of climate change, improving water quality and reducing GHGs' emissions, thus lowering environmental damages and enhancing social well-being. Manure fertilization and optimizing the use of synthetic fertilizers are important cost-effective policies increasing social benefits in a range between 50 and 160 million Euros. Results show that irrigation modernization increases the efficient use of nitrogen and water, augmenting social benefits by up to 90 million Euros, and enlarging stream flows at the river mouth. In contrast, manure treatment plants reduce private and social benefits even though they achieve the lowest nitrate concentrations. Our study provides insights on the synergies and tradeoffs between environmental and economic objectives. Another finding is that drought conditions decrease the effectiveness of policies, and increase the tradeoffs between water availability and nitrate pollution. The results contribute to the discussion of designing cost-effective policies for the abatement of agricultural polluting emissions into water and the atmosphere. Highlights: A novel integrated hydro-economic model for basin-scale optimal planning is developed in the Ebro River. Water scarcity and agricultural nonpoint pollution are addressed. Hydrological, economic and pollution features capture spatial and sectoral interactions. Climate change mitigation and adaptation policies address water scarcity and pollution abatement. Sustainable policies require collective action by stakeholders.